Pressure driven phase transition in 1T-TiSe2, a MOIPT+DMFT study. (February 2017) - Koley, S.
Abstract: The nature of unconventional superconductivity associated with charge density wave order in transition metal dichalcogenides is currently a debated issue. Starting from a normal state electronic structure followed by a charge ordered state how superconductivity in 1T-TiSe2 arises with applied pressure is still under research. A preformed excitonic liquid driven ordered state mediated superconductivity is found in broad class of TMD on the border of CDW. Using dynamical mean field theory with input from noninteracting band structure calculation, I show a phase transition appearing near about 2 GPa pressure at a temperature of 2 K as a result of exciton-phonon coupling. Abstract : Highlights: LDA+DMFT study of 1T-TiSe2 under different pressure. Calculation of DMFT Resistivity and optical conductivity both at different pressure. DMFT ARPES and Fermi surface calculation to show phase transition dependent changes in agreement with earlier study. DMFT self consistent calculation of superconducting order parameter.